Artificial Intelligence in History Education: Observations and Perspectives - Kovalets, Taras (My University, 2023)
Kovalets T. Artificial Intelligence in History Education: Observations and Perspectives // Науковий вісник Чернівецького національного університету імені Юрія Федьковича: Історія. Чернівці: Чернівецький університет, 2023. № 2. P. 143-148.